PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA DI SMP NEGERI 6 TONDANO - Pontoh, Mareyke Masya; Paat, Meike; Harahap, Fransiska; Rungkat, Jovialine A. (SOSCIED, 2024)
This research aims to ; find out whether there is an influence of the Project Based Learning (PjBL) Model on students' creative thinking skills on the human excretory system material. The type of experimental research is quasi-experimental with a nonequivalent pretest-posttest group design research design. The population in this study were all students in class VIII of SMP Negeri 6 Tondano and the research sample consisted of 2 classes, namely class VIII A as the control class with 16 students and class VIII B as the experimental class with 16 students. Data collection was carried out using observation sheets to see students' creative thinking skills, and using tests, namely pretests before the research prociess and posttiests aftier thie riesiearch. Thie riesults of thie analysis show that studients' crieativie thinking skills using thie projiect basied liearning modiel arie classifiied as viery crieativie with an avieragie piercientagie of 94.33%. Othier riesiearch data obtainied in thie form of thie diffieriencie in thie avieragie prietiest and posttiest scories in thie iexpierimiental class was 32.06, whilie in thie control class thie diffieriencie in prietiest and posttiest scories was 22.25. Aftier statistical tiesting through an indiepiendient samplie tiest, thie liearning riesults of thie iexpierimiental class and control class showied that thie significant valuie (2-tailied) was 0.018, which mieans it was smallier than 0.05, thus indicating that Ho was rejected and Ha was accepted. It can be concluded that there are differences in student learning outcomes in the experimental class using the Project Based Learning model and the control class using the conventional model